Pengembangan Media Pembelajaran Kotak Materi Puisi pada Teks Puisi Siswa Kelas X SMA Negeri 1 Moro Kabupaten Karimun Kepulauan Riau: Pengembangan Media Pembelajaran Kotak Materi Puisi pada Teks Puisi Siswa Kelas X SMA Negeri 1 Moro Kabupaten Karimun Kepulauan Riau - Sepni Arlinda; Abdul Malik; Zaitun; Isnaini Leo Shanty; Harry Andheska; Legi Elfitra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to develop learning media for poetry material boxes in poetry texts for class X students at Moro 1 State High School, Karimun Regency, Riau Islands. The research method that researchers use is a 4D model which consists of definition, design stage, up to the development stage only. In this research, the media developed is visual media in the form of a box. If you open the box, it will take the form of a cube net which is erected using supports. In the media there is poetry text material and games. The number of students from the small group trial was 6 students, and the large group was 40 students. Data collection techniques in this research used interviews, media validation questionnaires, material validation questionnaires, and media practicality questionnaires by students. The data analysis technique in this research uses qualitative descriptive to analyze comments, suggestions and several media inputs, while quantitative descriptive is used to calculate assessment scores for learning media products in the poetry material box. The results of the research showed that the results of the poetry material box learning media with a validation percentage from media experts reached 75% with the qualification "valid", and validation from material experts reached 85% with the qualification "very practical". Apart from that, a media practicality trial was carried out by students at SMA Negeri 1 Moro with the percentage of the small group reaching 86% with the qualification "very practical" and the large group reaching 80% with the qualification "practical".hu7